A Rare Case of Antithyroid Drug-Induced Lupus Erythematosus, Graves' Disease, and Primary Infertility - Kusuma, Singgih; Edi Susanto; Nova Kurniati; RM Dewi Anggraini (HM Publisher, 2025)
Background: Drug-induced lupus erythematosus (DILE) is a rare autoimmune disorder that mimics idiopathic lupus erythematosus, triggered by certain medications. This case report presents a patient with DILE induced by methimazole, a commonly used antithyroid drug, along with Graves' disease and primary infertility. Case presentation: A 41-year-old woman presented with palpitations, a history of Graves' disease treated with methimazole, and primary infertility. She developed lupus-like symptoms including fever, joint pain, and skin rash. Examination revealed tachycardia, tenderness of the right and left knee joints and limited range of motion. Laboratory investigations confirmed hyperthyroidism and autoimmune features consistent with DILE. Conclusion: This case highlights the rare occurrence of DILE induced by methimazole, emphasizing the importance of recognizing and managing this condition in patients receiving antithyroid drugs.